Psicoeducação para a prevenção do câncer de colo de útero: uma proposta de intervenção - Kühn, Claudia Helena Corazza (Universidade do Vale do Rio dos Sinos, 2014)
This essay is divided in two articles. One is based on a systematic literature review and the other is an empirical article. The aim of the first study was to conduct a systematic review of the international literature about psychological interventions based on the Common Sense Model. Five arcticles were selected from a total of 170 found. The results have shown that most of the studies are about psychological interventions focused on the the management of patients with chronical diseases and on the prevention of those diseases in healthy individuals. The second study aims to develop, apply and evaluate an intervention protocol using psychoeducation based on the Common Sense Model, with the purpose to acquire knowledge on cervical cancer, adjust risk perception, promote and enhance selfcare and change illness perception. Method: quasi-experimental design, with evaluation pre and post-intervention with women that use a health care center. The instruments were: Sociodemographic questionnaire, Self-Care Evaluation Scale (ASA-A), Brief Illness Perception Questionnaire (Brief IPQ), Risk Perception Questionnaire, Leaflet about cervical cancer. Results: The intervention allowed women to adjust their perception about the disease, increasing risk perception and reducing the perceived threat of the disease.
Keywords: Câncer de colo do útero; Intervenção psicoeducativa; Modelo do sendo comum; Cervical cancer; Common sense model; Psychoeducational intervention; ACCNPQ::Ciências Humanas::Psicologia